Generation Mechanism and Reduction Method of Induced Drag Produced by Interacting Wingtip Vortex System. (14th September 2017) - Zhang, M.; Wang, Y. K.; Fu, S.
Abstract : The formation and evolution of wingtip vortex system generated from three wing configurations are simulated with the improved delayed detached eddy simulation (IDDES) method. Numerical results show that each layout produces an interacting wingtip vortex system. These three corresponding vortical interactions are, respectively, the interaction between wingtip vortex and its counter-rotating vortex, winglet-tip vortex, and winglet four-vortex system. The fluid entrainment of ambient fluid and vortical impulse transport resulted from inductive effect have been founded generally existing in its formation and evolution. These two dominated mechanisms account for induced drag generation. On one hand, the winglet with toed-out angle is considered capable of changing the flow field around the winglet, and decomposing the winglet-tip vortex into four small vortices. Due to quite few fluid entrainment effects, this typical four-vortex system that cannot merge and only dissipate in the near wake scarcely contributes to the induced drag. On the other hand, a potential drag reduction method is also indicated that a lower induced drag can be obtained when the merger of wingtip and winglet-tip vortex is controlled and eliminated. This investigation will offer a novel perspective to guide the design of wingtip device and method of crusing resistance reduction for aircrafts.